2023
DOI: 10.21203/rs.3.rs-3213618/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific effects in how childhood exposures to multiple ambient air pollutants affect white matter microstructure development across early adolescence

Devyn Cotter,
Hedyeh Ahmadi,
Carlos Cardenas-Iniguez
et al.

Abstract: Ambient air pollution is ubiquitous, yet questions remain as to how it might impact the developing brain. Large changes occur in the brain’s white matter (WM) microstructure across adolescence, with noticeable differences in WM integrity in male and female youth. Here we report sex-stratified effects of fine particulate matter (PM2.5), nitrogen dioxide (NO2), and ozone (O3) on longitudinal patterns of WM microstructure from 9-13 years-old in 8,182 (49% female) participants using restriction spectrum imaging. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Previous studies by our research team have identified links between childhood air pollution and brain connectivity in adolescents from the ABCD Study ( Burnor et al, 2021 ; Sukumaran et al, 2023 ; Cotter et al, 2023b ; Cotter et al, 2023a ). The current analyses build upon these initial studies to include prenatal estimates in addition to childhood exposure, and utilizes a multivariate approach that allows for quantification of both joint and independent effects of highly correlated variables, such as co-exposures of different criterion pollutants from two different periods of neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies by our research team have identified links between childhood air pollution and brain connectivity in adolescents from the ABCD Study ( Burnor et al, 2021 ; Sukumaran et al, 2023 ; Cotter et al, 2023b ; Cotter et al, 2023a ). The current analyses build upon these initial studies to include prenatal estimates in addition to childhood exposure, and utilizes a multivariate approach that allows for quantification of both joint and independent effects of highly correlated variables, such as co-exposures of different criterion pollutants from two different periods of neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the developing brain may be especially sensitive to the neurotoxicant effects of ambient air pollution. Air pollution during the prenatal and childhood periods has been shown to impact the brain connectome ( Herting et al, 2019 ; Burnor et al, 2021 ; Sukumaran et al, 2023 ; Cotter et al, 2023b ; Pérez-Crespo et al, 2022 ; Binter et al, 2022 ; Lubczyńska et al, 2021 , 2020 ; Cotter et al, 2023a ; Peterson et al, 2022 ; Guxens et al, 2022 ). Defined as the spatial map of neural connections that give rise to function ( Shi and Toga 2017 ), the brain connectome can be characterized both structurally and functionally using multimodal neuroimaging methods, such as diffusion-weighted imaging (DWI) and resting-state functional magnetic resonance imaging (rs-fMRI) ( Power et al, 2011 ; Smith et al, 2009 ; Yeo et al, 2011 ; Laumann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation